PENGEMBANGAN MODUL KETERAMPILAN PSIKOLOGI UNTUK MEMBENTUK PENGASUHAN BERBASIS KOMUNITAS RAMAH REMAJA - Muslimah, Alfiana Indah; Hanoum, Magdalena (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2017)
Urban society is synonymous with people who master technology, rapid changes and the rhythm of life demanded fast-paced. Community-based care needs to be encouraged to keep teens out of negative currents. This study aims to determine the interventions that will then be undertaken to develop a psychology skill module in order to create a youth-friendly community. This research is a partial quantitative research with CBPR (Community Based Parsipatory Research) method. This method enables communities and academia to collaborate in determining the focus of interventions and targets to achieve together. The study involved adolescents, parents with teenagers, community members (neighbors) and community leaders to explore the need for interventions to create a youth-friendly environment. Methods of interviewing (semi-structured), focus group disscusion, behavioral and environmental observations and psychological measurements of parenting are a way for researchers to extract data from the community. The results showed that adolescents are able to grow their potential to develop the necessary community-based care.     Community-based care fosters active participation for the community. People need psychological skills, ie behavioral detection in adolescents (Deteksi), empathy (Empati), effective communication (Komunikasi efektif), action (Aksi) and responsiveness (Tanggap), which will be shortened by DEKAT. Youth-friendly communities are expected to guide youth to better express their aspirations and youthful energy